Dinuclear complexes of copper and silver with quinine - Hong, Nguyen Thanh; Dat, Bui Trong (Vietnam Journal of Chemistry, 2014)
The following silver and copper complexes in which quinine  is coordinated via the two possible donor atoms was prepared and characterized. Coordination of quinine via the hydroxyl oxygen and quinoline nitrogen is observed in C20H25N2O2Cu2(SO4)2.6H2Oand C20H25N2O2Ag2(SO4). The existence of the proton at the coordinated hydroxyl oxygen is also observed in these complexes. The coordination mode and the conformation of quinine can be derived from IR and Raman spectra and by using NMR techniques